Teaching English through Fun Learning Activities: A Service Program for Village Youths in Pantai Labu Deliserdang - Masruddin (EPISTEMOLOGI : JURNAL PENGABDIAN MASYARAKAT DAN PENELITIAN, 2025)
This community service program aimed to improve English language skills among village youths in Pantai Labu, Deliserdang, through the implementation of fun and interactive learning activities. Recognizing the limited access to formal English instruction in rural areas, the program focused on fostering a positive, engaging, and learner-friendly environment that emphasized communication over memorization. A thematic curriculum was developed, incorporating games, songs, role-plays, group projects, and creative tasks designed to introduce basic vocabulary and conversational skills. Conducted over four weeks, the program involved university student facilitators who acted as both educators and motivators. Results indicated noticeable improvements in learners’ vocabulary, confidence, motivation, and willingness to use English in daily interactions. Additionally, the program enhanced social collaboration and received strong support from the local community. While challenges such as time constraints and mixed ability levels were encountered, the outcomes suggest that fun learning approaches can effectively support language development in underserved communities. This initiative demonstrates the transformative potential of learner-centered, culturally sensitive education and offers a sustainable model for future outreach efforts.